Mitral valve prolapse - it"s possible to stratify prognosis in these patients?. (8th February 2021) - Silverio Antonio, P; Rodrigues, T; Santos, R; Nunes-Ferreira, A; Cunha, N; Couto Pereira, S; S Morais, P; Alves Da Silva, P; Valente Silva, B; Brito, J; Placido, R; David, C; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Mitral valve prolapse (MVP) is one of the most frequent causes of mitral valve disease in developed countries, traditionally with a benign prognosis, however some patients develop arrythmias and significant mitral regurgitation (MR) with need of intervention. Herein our purpose was to establish clinical, electrocardiographic and echocardiographic predictors of arrythmias, mitral valve intervention (MVI) and hospitalization in MVP patients to better characterize the prognosis in these patients. Methods: Single-center retrospective study of consecutive patients with MVP documented in transthoracic echocardiogram between January 2014 and October 2019. MVP was defined as systolic displacement of the mitral leaflet into the left atrium ≥ 2 mm from the mitral annular plane. Demographic, clinical, echocardiographic, electrocardiographic data were collected as well as adverse events at follow-up. The results were obtained using Chi-square and Student-t tests; predictors were found with logistic regression. Results: 247 patients were included (mean age 62.9 ± 18 years, 61% males), most with MVP involving the posterior leaflet (48.6%). 40% were symptomatic, 47.4% had more than moderate MR, and 25% had interventricular conduction delay in the ECG. During a mean follow-up of 30 ± 19 months, 38% had arrythmias, 27.1% needed mitral valve intervention (95% surgery and 5% percutaneous), 27.1% had atrial fibrillation (AF), 3.4% had ventricular arrythmias, 19.2% had ventricular premature beats, 13.3% had hospital admission for cardiovascular cause and 8.5% (n = 21) died. 9.3% of the patients had mitral annulus disjunction (MAD). Palpitations (p = 0.018), AF (p < 0.001), significant MR (p < 0.001), higher NYHA class (p = 0.016), systolic pulmonary artery pressure (SPAP) (p < 0.001), LV mass (p < 0.001), QTc (p = 0.01) and MAD maximum distance (p = 0.02) associated with MVI. MAD maximum distance value presented an excellent capacity to predict the MVI (AUC 0.85 p = 0.019); the best cut-off was 11, 5 mm (Sens = 80%; Spec = 83%). AF was a predictor of hospitalization in univariate analysis (OR = 2.57, CI95% 1.15-5.75, p = 0.022). Regarding arrhythmic events, we found association with aortic root dilatation (p = 0.032), NYHA III-IV (p = 0.013), age and LV mass (both with p < 0.001). In multivariate analysis, LV mass (OR = 1.02, CI95% 1.005-1.027, p = 0.005) and age (OR = 1.038, CI95% 1.004-1.053, p = 0.021) were independent predictors of arrythmias. In this sample, MAD was not associated with arrythmias. Conclusion: Opposing to previous studies in our population, MAD was not associated with arrythmias but had an excellent capacity to predict MVI. Age and LV hypertrophy were independent predictors of arrythmias in our patients. Larger studies are needed to better stratify patients with MVP, as its association with arrhythmias, hospitalization and the need for intervention is not negligible.